Application of Collagenolytic Proteases from Bacillus subtilis B13 and Bacillus siamensis S6 for Tenderizing Goat Meat during Wet Aging - Supaluk Sorapukdee; Wiwat Samritphol; Papungkorn Sangsawad; Pussadee Tangwatcharin (My University, 2024)
This research aimed to assess the effect of collagenolytic proteases from Bacillus subtilis B13 and Bacillus siamensis S6 for tenderizing goat meat during wet aging. Collagenolytic proteases B13 and S6 were prepared at 5 U/mL of collagenolytic activity before injecting into goat meat with 10% (v/w) of initial weight. The control sample was injected with distilled water and used as a negative control. The injected meats were placed in vacuum-sealed bags and wet aged at 4°C for 0, 3, 5, 7, 14, and 21 days. Thereafter, total aerobic count and physicochemical quality were elucidated. Both enzyme-treated samples from B13 and S6 aged for 5 days showed an acceptable microbial quality with lower than 5.7 Log CFU/g. These conditions produced the tender meats by the reduction in shear force accounting for 30% for B13 and 26% for S6 as compared to the control. Moreover, the enzyme-treated samples showed lower values of hardness, gumminess, and chewiness, with higher springiness and trichloroacetic acid-soluble peptides than the control (p<0.05). The detrimental impact on cooking loss and lipid oxidation was not found. Enzyme-injected meat had a lower cooking loss than the control (p<0.05) with no significant difference in lipid oxidation (p>0.05). Notably, meats treated with B13 and S6 were lower in CIE L* value as compared to the control (p<0.05) with no significant impact on CIE a* and CIE b* (p>0.05). These results suggested that these two collagenolytic proteases could enhance the quality of goat meat in terms of tenderness and reduce the aging time for meat tenderization.
Keywords: Bacillus (shape); Protein Hydrolysis and Bioactive Peptides